Deteksi Anaplasma sp. pada Anjing di Bali secara Klinis, Serologis, dan Molekuler (THE DETECTIONS OF ANAPLASMA SP. IN DOGS IN BALI WITH CLINICAL, SEROLOGICAL AND MOLECULAR) - Pradnyantari, Anak Agung Sagung Istri; Suartha, I Nyoman; Erawan, I Gusti Made Krisna; Mahardika, I Gusti Ngurah Kade (Jurnal Veteriner; Vol 20 No 4 (2019)DO - 10.19087/jveteriner.2019.20.4.479, 2019)
This study aims to determine the infection of Anaplasma sp. in dogs in Bali with clinical, serological and molecular detections. This research method uses Cross Sectional. The samples were collected from June 2017 to July 2018. The total number of samples obtained was 109 dogs from 3.563 samples from seven veterinarian clinics in Bali. Clinical examinations and blood tests are method of clinical detection. Serological detection is using a rapid test kit E. canis & Anaplasma spp. BioNote© production. Molecular detection have been using with the Polymerase Chain Reaction technique. PCR products were sequenced at 1st BASE Laboratories Sdn Bhd, Malaysia. Data were analyzed using the MEGA 4 program.  The results showed that Anaplasma sp. are present in dogs in Bali and can be detected by clinically (3,05%), serologically (55,04% base on clinically positive) and molecularly (42,20% base on clinically positive) detection. Thus, detected species Anaplasma sp. In Bali from this study can be identified as A. platys.